Dynamic Courtship Signals and Mate Preferences in Sepia plangon - López Galán, Alejandra; Chung, Wen-Sung; Marshall, N. Justin (Frontiers in Physiology, 2020)
Communication in cuttlefish includes rapid changes in skin coloration and texture, body posture and movements, and potentially polarized signals. The dynamic displays are fundamental for mate choice and agonistic behavior. We analyzed the reproductive behavior of the mourning cuttlefish Sepia plangon in the laboratory. Mate preference was analyzed via choice assays (n = 33) under three sex ratios, 1 male(M): 1 female(F), 2M:1F, and 1M:2F. We evaluated the effect of modifying polarized light from the arms stripes and ambient light with polarized and unpolarized barriers between the cuttlefish. Additionally, to assess whether a particular trait was a determinant for mating, we used 3D printed cuttlefish dummies. The dummies had different sets of visual signals: two sizes (60 mm or 90 mm mantle length), raised or dropped arms, high or low contrast body coloration, and polarized or unpolarized filters to simulate the arms stripes. Frequency and duration (sec) of courtship displays, mating, and agonistic behaviors were analyzed with GLM and ANOVAs. The behaviors, body patterns, and their components were integrated into an ethogram to describe the reproductive behavior of S. plangon. We identified 18 body patterns, 57 body patterns components, and three reproductive behaviors (mating, courtship, and mate guarding). Only sex ratio had a significant effect on courtship frequency, and the male courtship success rate was 80%. Five small (ML < 80mm) males showed the dual-lateral display to access mates while avoiding fights with large males; this behavior is characteristic of male "sneaker" cuttlefish. Winner males showed up to 17 body patterns and 33 components, whereas loser males only showed 12 patterns and 24 components. We identified 32 combinations of body patterns and components that tended to occur in a specific order and were relevant for mating success in males. Cuttlefish were visually aware of the 3D-printed dummies; however, they did not start mating or agonistic behavior towards the dummies. Our findings suggest that in S. plangon, the dynamic courtship displays with specific sequences of visual signals, and the sex ratio are critical for mate choice and mating success.